The Effect of Personality Traits and Life Skills of Physical Education and Sports Teacher Candidates on Pre-professional Teacher Identity - İnce, Uğur; Coşkuner, Zeki (ERCAN POLAT, 2025)
The aim of this study was to examine the effects of personality traits and life skills on the pre-professional teacher identity of prospective physical education and sports teachers. The research was conducted with 622 teacher candidates enrolled in Schools of Physical Education and Sports and Faculties of Sports Sciences at seven state universities in Türkiye. Data were collected using the Five Factor Personality Scale, the Life Skills Scale, and the Pre-Professional Teacher Identity Scale, and analyzed through t-test, ANOVA, correlation, and multiple regression techniques. The findings revealed that life skills and personality traits were significantly associated with pre-professional teacher identity. In particular, the subdimensions of life skills such as empathy, self-awareness, and communication skills were strong predictors of teacher identity. Among personality traits, extraversion, conscientiousness, agreeableness, and openness to experience contributed positively, while neuroticism did not have a significant effect. Additionally, differences were observed according to variables such as gender, type of sport, and work experience, indicating that both individual and contextual factors shape teacher identity development. In conclusion, the study demonstrates that the integration of life skills and positive personality dimensions plays a critical role in strengthening the professional identity of prospective physical education and sports teachers. These results highlight the need for teacher education programs, particularly in the field of sports sciences, to place greater emphasis on life skills training and the recognition of personality traits in order to support identity formation.
Keywords: Sports Science and Exercise (Other); Egzersiz ve Spor Bilimleri (Diğer)